2019
DOI: 10.1002/nbm.4156
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping of the spine using in‐phase echoes to initialize inhomogeneous field and R2* for the nonconvex optimization problem of fat‐water separation

Abstract: Quantitative susceptibility mapping (QSM) of human spinal vertebrae from a multi‐echo gradient‐echo (GRE) sequence is challenging, because comparable amounts of fat and water in the vertebrae make it difficult to solve the nonconvex optimization problem of fat‐water separation (R2*‐IDEAL) for estimating the magnetic field induced by tissue susceptibility. We present an in‐phase (IP) echo initialization of R2*‐IDEAL for QSM in the spinal vertebrae. Ten healthy human subjects were recruited for spine MRI. A 3D m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…R2 corrected water/fat separation estimating water, fat, and inhomogeneous field from gradient‐recalled echo (GRE) signal is a necessary step in quantitative susceptibility mapping to remove the associated chemical shift contribution to the field 1‐5 . Several algorithms, including hierarchical multiresolution separation, multi‐step adaptive fitting, and T2‐IDEAL, have been proposed to decompose the water/fat separation problem into linear (water and fat) and nonlinear (field and R2) subproblems and solve these problems iteratively 6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…R2 corrected water/fat separation estimating water, fat, and inhomogeneous field from gradient‐recalled echo (GRE) signal is a necessary step in quantitative susceptibility mapping to remove the associated chemical shift contribution to the field 1‐5 . Several algorithms, including hierarchical multiresolution separation, multi‐step adaptive fitting, and T2‐IDEAL, have been proposed to decompose the water/fat separation problem into linear (water and fat) and nonlinear (field and R2) subproblems and solve these problems iteratively 6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…For Dixon MRI data, the post‐processing algorithm was developed in MATLAB (r2016a, MathWorks, Natick, Massachusetts). Multiple echo complex images were rebuilt from real and imaginary images, then the water and fat images were estimated according to the iterative least‐squares algorithm (IDEAL, iterative decomposition of water and fat with echo asymmetry and least‐squares estimation) 21,30 . Complex signal over echo time S ( T E n ) extracted pixel by pixel, containing water and fat species, can be expressed as 31,32 normalS()TEn=()W+Fρ=1Prρ0.25emei2πfρ0.25emTnormalEnei2italicπψTnormalEn0.25emeR2*TnormalEn. …”
Section: Methodsmentioning
confidence: 99%
“…Multiple echo complex images were rebuilt from real and imaginary images, then the water and fat images were estimated according to the iterative leastsquares algorithm (IDEAL, iterative decomposition of water and fat with echo asymmetry and least-squares estimation). 21,30 Complex signal over echo time S(T En ) extracted pixel by pixel, containing water and fat species, can be expressed as 31,32 S…”
Section: Image Processingmentioning
confidence: 99%
“…The effects of relaxation time differences are known to bias the estimation of proton density fat-fraction (PDFF), 37 , 38 but are generally neglected in QSM. 12 , 23 , 24 , 28 To minimize the bias caused by T 1 relaxation rate differences, small FAs have to be used, resulting in poor SNR, or a correction based on known T 1 values 38 can be applied. In the case of PDFF mapping of the iron overloaded liver, the differences in are assumed to be negligible 39 due to the shortening of the values being dominated by the presence of iron.…”
Section: Introductionmentioning
confidence: 99%
“…Although a single-peak fat signal model is assumed in generating the spectrally selective radiofrequency (RF) pulses in SMURF, it has been shown that this approximation does not lead to significant bias in QSM outside the brain. 23 Susceptibility values of fatty tissues vary, however, quite widely in the literature, 23 e.g., 0.29 ppm 7 and 0.57 ppm 9 for the fat in the liver, 0.19 ppm 21 for the fat in the knee, and 0.29 ppm 24 for the fatty fascia in the head-and-neck. Nevertheless, in all cases was the fat assessed as being more paramagnetic than the surrounding water-based tissues.…”
Section: Introductionmentioning
confidence: 99%